Language learning strategies used by Indonesian learners in IELTS - Juli Yanti Damanik (Universitas Syiah Kuala, 2022)
This study investigated the frequently used language learning strategies (LLS) by Indonesian learners in learning English for a high-stakes exam, IELTS. In addition, differences in the LLS use among participants with different proficiency were examined. Using a quantitative approach, data were collected by using an online survey by utilizing Oxford’s Strategy Inventory for Language Learning (SILL) as the instrument. Sixty-one Indonesian adult learners who had taken IELTS were involved in this study. Their IELTS score indicated their proficiency levels. Data analysis was carried out using Statistical Package for Social Science (SPSS). It involved a descriptive analysis to find the frequency and an independent samples t-test to see the LLS use based on proficiency. The findings revealed that the participants used various LLS in learning English for IELTS. The most frequently used strategies were metacognitive, followed by cognitive, compensative, social, affective, and memory strategies. Meanwhile, the independent samples t-test showed that the difference in the LLS use among participants with different proficiency was not noticeable. Reflecting on the results, it is proposed that English teachers in Indonesia may start growing their learners’ awareness of LLS benefits and teach them to use them properly in their learning English for IELTS.